LA UNIVERSIDAD PÚBLICA EN LA SOCIEDAD DEL CONOCIMIENTO - Ugarte Vega Centeno, Máximo (2013)
The debate about the university is still in force, the current situation is worrying for many internal and external factors that influence its management and its development prospects for the future in a changing society, in which the university must keep up the events to respond and fulfill the role assigned to it in society.